Assessing the political vulnerability of National Parks in sub-Saharan Africa using data on digital trends and engagement - Azevedo, Karoline; Alves-Martins, Fernanda; Martinez-Arribas, Javier; Correia, Ricardo A.; Malhado, Ana C. M.; Ladle, Richard (WILEY, 2025)
1. National Parks (NPs) and other protected areas in sub-Saharan Africa are crucial in attracting international tourists interested in wildlife tourism, contributing to national economies. Despite their cultural, economic, and conservation significance, these areas face diverse development threats, leading to pressures for protected area downgrading, downsizing, or degazettement (known as PADDD).
2. We comprehensively analyse the geographical, historical, and structural aspects of 322 NPs in sub-Saharan Africa and assess their political vulnerability by exploring the interplay of development pressures and public interest (as measured through Wikipedia page views).
3. Fewer than 30% of these NPs possess or report information regarding management plans, even among the five most frequently viewed areas on Wikipedia. This is particularly concerning, since among those who underwent a PADDD event (51 NPs), almost 90% of them also had no information about the existence of management plans.
4. Although we did not identify a statistically significant association between tourism and public interest online, tourism emerges as a potential mitigating factor against PADDD, along with high levels of peace.
5. NPs that garner significant public interest online do not share the same socio-geographic profile as parks that are most resilient to PADDD events. While digital metrics of public interest have potential as indicators of political resilience in NP, our research has shown that these metrics need refinement to fully understand which biophysical and cultural aspects of parks attract more public attention. Overall, effective conservation strategies in sub-Saharan Africa require a more holistic understanding of historical, socio-economic, and cultural factors.
Read the free Plain Language Summary for this article on the Journal blog.